1980
DOI: 10.1039/dt9800001342
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and electronic properties of ammine[tris(2-aminoethyl)amine]copper(II) diperchlorate and potassium penta-amminecopper(II) tris(hexafluorophosphate)

Abstract: Crystal Structure and Electronic Properties of Ammine[tris(2-aminoethyl)amine]copper(i~) Diperchlorate and Potassium Penta-amminecopper( 11) Tris( hexaf luorophosphate)By M a r y Duggan, Noel Ray, Brian Hathaway,' and (in part)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
126
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(148 citation statements)
references
References 0 publications
21
126
1
Order By: Relevance
“…In all cases, the d-d transitions were at a higher energy than those reported for Cu(II) complexes based on classical tren ligands (Ϸ880 nm) (38,46), which is a reflection (54,55) (Fig. 9, which is published as supporting information on the PNAS web site) yielded straight lines with a slope n ϭ 1, confirming the formation of adducts with a 1:1 stoichiometry.…”
Section: Synthesis and Spectroscopic Characterization Of The Calix[6]mentioning
confidence: 63%
See 1 more Smart Citation
“…In all cases, the d-d transitions were at a higher energy than those reported for Cu(II) complexes based on classical tren ligands (Ϸ880 nm) (38,46), which is a reflection (54,55) (Fig. 9, which is published as supporting information on the PNAS web site) yielded straight lines with a slope n ϭ 1, confirming the formation of adducts with a 1:1 stoichiometry.…”
Section: Synthesis and Spectroscopic Characterization Of The Calix[6]mentioning
confidence: 63%
“…3, shows a copper center coordinated to the four nitrogen atoms of the calix [6]tren ligand and to one molecule of EtOH buried inside the calixarene cavity. The geometry at the metal center is trigonal bipyramidal (TBP) with a distorsion ( ϭ 0.70) (37) slightly more pronounced than those reported for other trenbased Cu(II) complexes (38)(39)(40)(41)(42)(43). For these classical systems, the angles between the axial ligands are always very close to 180°, whereas, in the calixarene system, the distortion of the TBP stems mainly from the low value of this angle (168.8°).…”
Section: Synthesis and Spectroscopic Characterization Of The Calix[6]mentioning
confidence: 87%
“…The magnetically-dilute polycrystalline complex (2) exhibits a reversed electron paramagnetic resonance (EPR) spectrum expected for a Cu" dopant having approximately trigonal-bipyramidal coordination geometry (Duggan, Ray, Hathaway, Tomlinson, Brint & Pelin, 1980). Simulation studies using the program QPOWA (Belford, 1987) show these spectra are consistent with a single Cu" dopant site having the parameters g± = 2.145, A.…”
mentioning
confidence: 64%
“…[20][21][22][23] It has been widely observed that regular and distorted trigonal bipyramidal copper(II) complexes exhibit an absorption band at > 670 nm, whereas square-pyramidal copper(II) complexes show an absorption band at considerably shorter wavelength. [20][21][22] Therefore, the coordination geometry may be considered intermediate between TBP and SP in the solid state. Unfortunately, we Notes were unable to isolate single crystals of the complex suitable for X-ray work.…”
Section: Resultsmentioning
confidence: 99%